Malnutrition Prevention in Islamic Perspective - Dadang Herdiansyah; Nurmalia Lusida; Nadilla Firda; Tria Astika Endah Permatasari; Abul A’la Al Maududi (Indonesian Journal of Islam and Public Health, 2022)
Malnutrition (malnutrition) is a major problem in the health sector, especially in developing countries. One of the health problems that threatens Indonesian children is malnutrition, therefore the government continues to take serious efforts to reduce the number of malnutrition, both in terms of economic health and education. Islam is a religion that upholds human values and emphasizes the importance of maintaining health and the food consumed by humans every day. Prevention of malnutrition related to the benefit of religion, it can be said that by consuming good and balanced nutrition that we have carried out Allah's commands in the Qur'an, to always eat good and halal food, pay attention to the nutrition contained, not to overdo it, and we know that Allah does not like and forbids us to leave a weak generation. Islam teaches how we choose food, consume food in moderation not excessively and recommends consuming food according to the diet taught by the Prophet SAW. Islam emphasizes that the food consumed by humans must meet two important criteria, namely good and halal, the food we consume must be selected so that it can help body growth and health.